2022
DOI: 10.1186/s12889-022-13477-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 skepticism and SARS-CoV-2 vaccine hesitancy: findings from a national population survey of U.S. adults

Abstract: Background The enduring presence of COVID-19 skepticism and SARS-CoV-2 vaccine hesitancy is an ongoing impediment to the global response effort to the current pandemic. This study seeks to identify determinants of skepticism and vaccine hesitancy in U.S. adults. Methods Data are from the Values and Beliefs of the American Public Survey, conducted in 2021 by the Gallup Organization in conjunction with Baylor University. The survey used stratified ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
3
15
0
4
Order By: Relevance
“…Political beliefs are a direct and negative predictor of vaccination behavior, while the direct effect of religious beliefs on vaccination behavior is non -significant. A similar finding was also reported in Levin and Bradshaw’s 6 study which found that, after adjusting for effects of sociodemographic variables, conservative political beliefs are still a significant predictor of COVID-19 vaccine hesitancy, while conservative religious beliefs are not. The present study corroborated that political beliefs have a much stronger impact than religious beliefs on COVID-19 vaccination, indicating that COVID-19 vaccination has indeed been politicized.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Political beliefs are a direct and negative predictor of vaccination behavior, while the direct effect of religious beliefs on vaccination behavior is non -significant. A similar finding was also reported in Levin and Bradshaw’s 6 study which found that, after adjusting for effects of sociodemographic variables, conservative political beliefs are still a significant predictor of COVID-19 vaccine hesitancy, while conservative religious beliefs are not. The present study corroborated that political beliefs have a much stronger impact than religious beliefs on COVID-19 vaccination, indicating that COVID-19 vaccination has indeed been politicized.…”
Section: Discussionsupporting
confidence: 86%
“…Numerous studies have been done on COVID-19 vaccination, but most have focused on intentions to receive a COVID-19 vaccine 3 - 5 or similar decision-related constructs such as COVID-19 vaccine hesitancy 6 or COVID-19 vaccine acceptance. 7 Although vaccine intention/hesitancy/acceptance are commonly used as proxies for the actual vaccine-intake behavior, these constructs do not always translate into action.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, a stronger sense of collective responsibility was associated with lower odds of intention to get vaccinated in the next three to five years, which is not consistent with previous literatures supporting the role of altruistic motives in vaccine uptakes [ 31 , 52 ]. Finally, political ideology was not found to be a significant predictor of two intention outcomes, despite the strong connection between individuals’ political ideology and COVID-19 vaccine issues [ 18 , 53 55 ]. This might have something to do with the relatively young ages of survey participants.…”
Section: Study 2 Discussionmentioning
confidence: 99%